2014
DOI: 10.2136/sssaj2013.09.0392
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Near Soil Surface Characteristics on Soil Detachment by Overland Flow in a Natural Succession Grassland

Abstract: All rights reserved. No part of this periodical may be reproduced or transmitted in any form or by any means, electronic or mechanical, including photocopying, recording, or any information storage and retrieval system, without permission in writing from the publisher. Permission for printing and for reprinting the material contained herein has been obtained by the publisher. Effects of Near Soil Surface Characteristics on Soil Detachment by Overland Flow in a Natural Succession Grassland Soil & Water Manageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 30 publications
(53 reference statements)
0
56
1
Order By: Relevance
“…Wang et al (2013b) reported that the steady infiltration rate was significantly negatively correlated with BSC thickness, BD, and Cl, and it was positively related to RD. All these results indicated that soil erodibility was likely altered greatly by any changes in near soil surface characteristics produced by vegetation restoration and afforestation (Wang et al, 2013a(Wang et al, , 2014b(Wang et al, , 2018a. Gao et al (2017) demonstrated that soil erodibility reflected by the K factor decreased significantly with the development of BSCs, mainly due to the increase in OM on the Loess Plateau.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Wang et al (2013b) reported that the steady infiltration rate was significantly negatively correlated with BSC thickness, BD, and Cl, and it was positively related to RD. All these results indicated that soil erodibility was likely altered greatly by any changes in near soil surface characteristics produced by vegetation restoration and afforestation (Wang et al, 2013a(Wang et al, , 2014b(Wang et al, , 2018a. Gao et al (2017) demonstrated that soil erodibility reflected by the K factor decreased significantly with the development of BSCs, mainly due to the increase in OM on the Loess Plateau.…”
Section: Introductionmentioning
confidence: 90%
“…BSCs, plant litter, root system, and soil physicochemical properties are important near soil surface characteristics of vegetation covered lands (Cerdà, 1996b;Bryan, 2000;Wang et al, 2014bWang et al, , 2015Wang et al, , 2017aWang et al, , 2017b. BSCs, plant litter, root system, and soil physicochemical properties are important near soil surface characteristics of vegetation covered lands (Cerdà, 1996b;Bryan, 2000;Wang et al, 2014bWang et al, , 2015Wang et al, , 2017aWang et al, , 2017b.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant roots are another important factor affecting DC by overland flow (De Baets et al, 2006;De Baets and Poesen, 2010). The effectiveness of roots in reducing detachment to flowing water is closely related to its physically binding and chemically bonding effects (Prosser et al, 1995;Wang et al, 2014b).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The effectiveness of BSCs in reducing soil detachment was closely related to the hydraulics of overland flow. BSCs failed to protect the soil from scouring when flow shear stress was greater than 11 Pa (Wang et al , ).…”
Section: Introductionmentioning
confidence: 99%